2015
DOI: 10.1590/s1677-5538.ibju.2014.0046
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a Chinese Version of Urinary Tract Infection Symptom Assessment Questionnaire

Abstract: Objectives:Our study evaluates the reliability and validity of a Chinese version of the Urinary Tract Infection Symptom Assessment questionnaire (UTISA).Material and Methods:Our study enrolled women who were diagnosed with uncomplicated urinary tract infection (uUTI) at clinics. The Chinese version of UTISA was completed upon first visit to the clinic for uUTI and at 1-week follow-up. We enrolled 124 age-matched women without uUTI from the community as the control group. The UTISA consists of 14 items (seven s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Either the original English or the translated versions in different languages (Uzbek, Russian, Italian, Chinese) of the UTISA were used as primary or additional symptom-assessment tools in studies [47][48][49][50][51]. Although the authors of the original UTISA did not aim to establish a cutoff value to differentiate between AC and other conditions, Chang et al [51] revealed such a cutoff value using the total summary score in a translated and validated Chinese version of the UTISA, using receiver operating characteristic-curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Either the original English or the translated versions in different languages (Uzbek, Russian, Italian, Chinese) of the UTISA were used as primary or additional symptom-assessment tools in studies [47][48][49][50][51]. Although the authors of the original UTISA did not aim to establish a cutoff value to differentiate between AC and other conditions, Chang et al [51] revealed such a cutoff value using the total summary score in a translated and validated Chinese version of the UTISA, using receiver operating characteristic-curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations in our study. The major limitation is that the study is a retrospective review, which is biased in its nature and we did not use a validated symptom score to evaluate the symptoms of the enrolled subjects. Although we excluded urine specimens that were not performed within 4 hours of the collection of the specimen, recent antibiotics use and also the factors that may have compromised the results.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of all UTIs occur in women and 20% to 30% of women with a UTI will experience recurrence. 16 Nowadays the incidence of recurrence is increasing and usually low dose antibiotic prophylaxis for several months are recommended. But antibiotic use is associated with the development of antibiotic resistance and the occurrence of side effects.…”
Section: Discussionmentioning
confidence: 99%